Leading groups: Leadership as a group process. (January 2013) - Thomas, Geoff; Martin, Robin; Riggio, Ronald E.
Although leadership is fundamentally a social psychological (and group) phenomenon, interest in the social psychology of leadership has waxed and waned over the years. The present article briefly reviews this chequered history and then discusses recent theoretical and empirical developments that extend the study of social cognition and social identity to the domain of leadership. In addition, we consider how the eight empirical articles that constitute this Special Issue relate to, and further, the study of leadership as a group process, and conclude by identifying fertile areas for future research.